Rumah Kita Foundation Communication Model in Improving the Quality of Non-Formal Education in Subulussalam City - Indah Yani; Tengku Walisyah (Universitas Muhammadiyah Enrekang, 2023)
This study aims to determine the communication model the Rumah Kita Foundation uses to improve the quality of non-formal education in Subulussalam City. This research uses a qualitative method with a descriptive approach. The data collection techniques used in this study were observation, interviews, online searches such as the Rumah Kita Foundation's social media, and documentation supported by theory obtained from books and journals. This research involved several parties to become research informants, namely the founders of the Rumah Kita Foundation, the Management of the Rumah Kita Foundation, and the community involved in the coaching activities carried out by the Rumah Kita Foundation. The research results show that the communication model used by the Rumah Kita Foundation is relevant to the communication model proposed by Harold Laswell, namely: first, Who, in this case, the Rumah Kita Foundation is the communicator and involves several parties who are competent in developing non-formal education programs. Second, the Says What Program, run by the Rumah Kita Foundation, is designed to be a solution by dividing non-formal education programs into three groups: children's education, family education, and community education. Third, Which Channel is the media used to run and promote the program, namely social media such as YouTube and Instagram, which also play an active role. Fourth, to the recipients of the message or those who experience the Rumah Kita Foundation program, namely the village community, children, and youth in Subulussalam City. Fifth, With What Effect, the influence or effect obtained is that Rumah Kita Foundation assisted villages can already produce their products thanks to their training.